Characteristics of Dental Services in Rural, Suburban, and Urban Areas Upon the Implementation of Indonesia National Health Insurance - Dewanto, Iwan; Koontongkaew, Sittichai; Widyanti, Niken (Frontiers in Public Health, 2020)
Introduction: The implementation of Indonesia National Health Insurance (NHI) for oral health needs to be evaluated by observing the dental disease patterns and dental therapy patterns from community health centers (CHCs) in the rural area, suburban area, and urban area. The aim of the study is to describe the characteristics of dental services in rural, suburban, and urban areas after the implementation of NHI on CHCs in the Special Region of Yogyakarta in 2014. Materials and methods: This is an observational study with a cross-sectional research design. The study used quantitative data obtained from dental records at selected CHCs. Using a purposive sampling method, 30 CHCs as unit analysis were collected from rural, suburban, and urban areas. The data were collected from January 2014 to December 2014. Results: Data from 26,554 patients were collected from dental records of dental clinics at CHCs. There were 5829 patient dental records from rural areas, 12,327 from suburban areas, and 8938 from urban areas. The primary dentist tends to provide services without clinical intervention on periodontal problems, abscesses, and lesions. Clinical interventions were mostly provided for prolonged retention and deposits on teeth. Primary dentists in suburban areas tend to provide clinical intervention on caries disease compared to those in rural and urban areas. Statistically significant differences (p < 0.05) were observed among locations in the pattern of providing clinical interventions on caries, abscess, lesion, prolonged retention, deposits on teeth, and other problems. No difference was recorded only on periodontal disease. Discussion: This study found that each area has different characteristics of dental disease and dental therapy patterns. Each area has a significant difference in the pattern of the clinical intervention of dental disease except in periodontal problems.